Wastewater monitoring system in the textile industry - Raditya, Murry; Pratama, I Putu Eka Widya; Bagastyo, Arseto Yekti; Nurhayati, Ervin; Kalahari, Bintang (Institute of Advanced Engineering and Science, 2024)
Recently, a problem which often experienced by the Environmental Agency is to monitor the quality of industrial waste. The problem comes from manual monitoring of wastewater and the high cost of laboratory tests for each variable for the waste. This system is intended to develop a wastewater monitoring system considering the state of the environment and technology. This system uses 5 types of sensors to measure the quality of wastewater. The sensor will display measurement data both offline via liquid crystal display (LCD) and online via the website. For the pH sensor test, we obtained an error value approximately of 1.32% and accuracy of 98.68%. For the oxidation reduction potential (ORP) sensor test, we obtained an error value of 1.4% with 98.6% accuracy. We obtained an error value of 0.22% with 99.78% accuracy for the temperature sensor test. For the total dissolved solid (TDS) sensor test, we obtained an error value of 1.02% with 98.98% accuracy. The color sensor is validated using a spectrometer to measure the variation of color in remazol waste concentration. For the Client - Server communication test, the system has a delay of 2 seconds. One of the advantages of using a web server is the system has minimum network traffic.